Evaluation of renal osteodystrophy in the dental clinic by assessment of mandibular and phalangeal cortical indices - Massahud, Bruna Correa; Guimares Henriques, Joao Cesar; Jacobs, Reinhilde; Rosa, Rafaela Rangel [UNESP]; Bardi Matai, Caio Vinicius [UNESP] (Springer, 2018)
Objectives Secondary perparathyroidism (SHPT) is a disease that affects patients with chronic kidney disease, and is characterized by mineral disturbance and bone loss, known as renal osteodystrophy. The aim of this study was to assess the validity of using intraoral phosphor storage plates to take radiographs of the middle phalanges to evaluate bone loss resulting from SHPT during follow-up of these patients. Methods The sample consisted of 24 patients with chronic kidney disease, 12 with parathyroid hormone (PTH) levels >= 500 pg/ml, and 12 with PTH levels < 500 pg/ml, who underwent hemodialysis weekly. For each patient, a panoramic radiograph and digital radiographs of the ring, index, and middle fingers of both hands were taken. The Mandibular Cortical Index (MCI) and the Trabecular Bone Pattern Index (TBP) were applied to the panoramic radiographs, while the Phalangeal Cortical Index (PCI) was applied to the digital radiographs of the phalanges. Three evaluators performed all analyses. Results Significant correlations were found between the PTH levels and the MCI (p = 0.023), the PCI (p = 0.039) and the TBP index (p = 0.032). These parameters were also significantly interrelated (MCI x PCI = 0.001; MCI x TBP = 0.004 and PCI x TBP = 0.009). The PCI was shown to have the highest correlation with PTH levels. Conclusion In patients with chronic renal disease, it is clinically relevant to use panoramic and digital radiographs using intraoral storage plates to assess a number of quantitative parameters that can be linked to PTH levels.
Keywords: Chronic kidney disease; Secondary hyperparathyroidism; Renal osteodystrophy; Dental radiography; Phalanges of the fingers